Quality requirements for MRI simulation in cranial stereotactic radiotherapy: a guideline from the German Taskforce “Imaging in Stereotactic Radiotherapy” - Putz, Florian; Bock, Michael; Schmitt, Daniela; Bert, Christoph; Blanck, Oliver; Ruge, Maximilian I.; Hattingen, Elke; Karger, Christian P.; Fietkau, Rainer; Grigo, Johanna; Schmidt, Manuel; Bäuerle, Tobias; et al. (Strahlentherapie und Onkologie, 2024)
Accurate Magnetic Resonance Imaging (MRI) simulation is fundamental for high-precision stereotactic radiosurgery and fractionated stereotactic radiotherapy, collectively referred to as stereotactic radiotherapy (SRT), to deliver doses of high biological effectiveness to well-defined cranial targets. Multiple MRI hardware related factors as well as scanner configuration and sequence protocol parameters can affect the imaging accuracy and need to be optimized for the special purpose of radiotherapy treatment planning. MRI simulation for SRT is possible for different organizational environments including patient referral for imaging as well as dedicated MRI simulation in the radiotherapy department but require radiotherapy-optimized MRI protocols and defined quality standards to ensure geometrically accurate images that form an impeccable foundation for treatment planning. For this guideline, an interdisciplinary panel including experts from the working group for radiosurgery and stereotactic radiotherapy of the German Society for Radiation Oncology (DEGRO), the working group for physics and technology in stereotactic radiotherapy of the German Society for Medical Physics (DGMP), the German Society of Neurosurgery (DGNC), the German Society of Neuroradiology (DGNR) and the German Chapter of the International Society for Magnetic Resonance in Medicine (DS-ISMRM) have defined minimum MRI quality requirements as well as advanced MRI simulation options for cranial SRT.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Brain metastases; DEGRO; DGMP; DGNC; DGNR; DS-ISMRM; Guideline; Meningioma; MRI simulation; Pituitary adenoma; Stereotactic radiosurgery; Stereotactic radiotherapy; Trigeminal neuralgia; Vestibular schwannoma